RELIGION, THE COVID-19, AND HEALTH PROTOCOLS: A CASE STUDY OF MUSLIMS GROUP VIEWS - Faizin, Afwan (ILMU USHULUDDIN, 2023)
The article aims to describe the religious views of Indonesian Muslim groups concerning Covid-19 and health protocols. It also explores the factors that lead some Muslims to reject health protocols in their religious practices. The qualitative method was employed in this study, with research subjects selected through purposive sampling, and data were analyzed using descriptive analysis. The informants included leaders of Indonesian Muslim groups, such as Muhammadiyah, Nahdlatul Ulama, and other Muslim group leaders. The research findings indicate that most Muslim group leaders interpret Islamic teachings with academic perspectives, although many tend to adopt conservative interpretations. This conservative religious understanding is influenced by several factors: first, the psychological factor of panic or cultural shock among some Muslims; second, the influx of information on social media whose accuracy is challenging to verify; third, economic pressure on the people; and fourth, the government’s indecisiveness and the ineffectiveness of public communication.